Aerodynamics in motorsports - Katz, J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
Motor racing, like other popular forms of competitive sports, requires physical fitness, concentration, and vigorous preparation and training. Although progress in technology may dominate the race, governing bodies are continuously updating the rulebooks to keep the human factor dominant in winning races. On the other hand, vehicle performance depends on elements such as the engine, tires, suspension, road, and aerodynamics. In recent years, however, vehicle aerodynamics has gained increased attention, mainly due to the utilization of the negative lift (downforce) principle, yielding several significant performance improvements. The importance of drag reduction and improved fuel efficiency are easily understood by the novice observer and are still at the center of racing vehicle design. Interestingly, however, generating downforce by the vehicle usually increases its drag but improves average speed in closed circuits. Consequently, various methods to generate downforce such as inverted wings, diffusers, and vortex generators will be discussed. Also, generic trends connecting a vehicle`s shape to its aerodynamics are presented, followed by more specific race-car examples. Due to the complex geometry of these vehicles, the aerodynamic interaction between the various body components is significant, resulting in vortex flows and wing shapes which may be different than those used on airplanes.